Pengaruh Kesehatan Mental Siswa terhadap Motivasi Belajar di SMK Farmako Medika Plus - M Dahlan R.; Mulan Alfipah (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
The purpose of this study was to determine the effect of mental health on learning motivation at SMK Pharmako Medika Plus. Innthissstudy, aaquantitativeeapproachwwas useddwithhtheecorrelational research method. Total population 44 students. The statement questionnaire was developed in 30 items and given to each sample, after conducting validity and reliability tests, linear regression analysis was carried out in SPSS 26. The resultssshoweddthat thereewassa moderate or sufficient effecttbetweennmental health on learning.motivation at SMK Pharmako Medika Plus, this is obtained from the rxy result of 0.688. Keywords: Learning, Mental Health, Motivation